Early detection of subtle motor dysfunction in cognitively normal subjects with amyloid-β positivity - Mollica, Maria A.; Tort-Merino, Adrià; Navarra, Jordi; Fernández-Prieto, Irune; Valech, Natalia; Olives, Jaume; León, María; Lleó, Alberto; Martínez-Lage, Pablo; Sánchez-Valle, Raquel; Molinuevo, José L.; Rami, Lorena (Cortex, 2019)
Since the current neuropsychological assessments are not sensitive to subtle deficits that may be present in cognitively normal subjects with amyloid-β positivity, more accurate and efficient measures are needed. Our aim was to investigate the presence of subtle motor deficits in this population and its relationship with cerebrospinal fluid (CSF) amyloid-β levels. We adapted the Finger Tapping Task to measure tapping speed and intrasubject variability. Seventy-two right-handed participants completed the study. Subjects were divided into three groups according to their CSF biomarker profile: 37 control participants (negative CSF AD biomarkers, CTR), 20 cognitively normal subjects with amyloid-β positivity (abnormal levels of CSF Aβ42, Aβ+) and 15 AD patients. All subjects underwent lumbar puncture for the CSF analysis, apolipoprotein E genotyping and completed the Finger Tapping Task, a neuropsychological battery and cardiovascular risk factor and physical activity assessments. An overall difference between groups was found both in tapping speed [F(2,66) = 19.37, p < .01] and in intrasubject variability [F(2,66) = 11.40, p < .01]. More specifically, the Aβ+ group showed lower speed [F(1,52) = 5.33, p < .05] and greater intrasubject variability [F(1,52) = 8.48, p < .01] than the CTR group, and higher speed than the AD group [F(1,30) = 13.61, p < .01]. Speed (β = .263, p < .05) and intrasubject variability (β = −.558, p < .01) were significantly associated with CSF amyloid-β levels. The present findings suggest that subtle motor difficulties can be detected in cognitively healthy subjects with amyloid-β positivity and be related to CSF Aβ42 levels. An accurate assessment of motor functions could help on identifying individuals at the earliest stage of the Alzheimer's continuum.